Evaluation of carbon accrual in afforested agricultural soils - Morris, Sherri J., author; Haile-Mariam, Shawel, author; Bohm, Sven, author; Paul, Eldor A., author; Blackwell Publishing Ltd., publisher (Colorado State University. Libraries, 2007)
Afforestation of agricultural lands can provide economically and environmentally realistic C storage to mitigate for elevated CO2 until other actions such as reduced fossil fuel use can be taken. Soil carbon sequestration following afforestation of agricultural land ranges from losses to substantial annual gains. The present understanding of the controlling factors is inadequate for understanding ecosystem dynamics, modeling global change and for policy decision-makers. Our study found that planting agricultural soils to deciduous forests resulted in ecosystem C accumulations of 2.4 Mg C ha-1 yr-1 and soil accumulations of 0.35 Mg C ha-1 yr-1. Planting to conifers showed an average ecosystem sequestration of 2.5 and 0.26 Mg C ha-1 yr-1 in the soils but showed greater field to field variability than when planted to deciduous forest. Path analysis showed that Ca was positively related to soil C accumulations for both conifers and deciduous afforested sites and played a significant role in soil C accumulations in these sites. Soil N increases were closely related to C accumulation and were two times greater than could be explained by system N inputs from atmospheric deposition and natural sources. Our results suggest that the addition of Ca to afforested sites, especially conifers, may be an economical means to enhance soil C sequestration even if it does not result in increasing C in aboveground pools. The mechanism of N accumulation in these aggrading stands needs further investigation.
Keywords: cations; deciduous forest; land-use change; pine forest; afforestation; soil organic matter; soil nitrogen; agriculture; carbon sequestration